USING DIFFERENT LOCAL ISOLATED LACTIC ACID BACTERIA TO RESIST BILE SALTS AND REDUCING ACHOLESTEROL - Ghanim M. H (Mesopotamia Journal of Agriculture)
Bifidobacterium sp. and Lact. acidophilus bacteria were isolated from newly born infant’s stool while Lact. plantarum bacteria were isolated from pickles . As for Lact, bulgaricus and Strep. thermophilus bacteria , they were isolated from local sheep yoghurt and identified by studying the morphological and biochemical tests . Then they were compared with Bergey’s Manual ( 1986 ) informations .The resistance of the above-mentioned bacteria to bile salt at aconcentration of 1 and 2% and the effect of these salts on the growth of bacteria were all studied . At the concentration of 2% , there was a reduction in the number of bacteria with the increase in exposing time to bile salt . At the concentration of 1% , the imported Bifidobacterium sp. was the most resistant to bile salt . On the other hand , Lact, bulgaricus and Strep. thermophilus were the least one . All bacteria showed ability in reducing cholesterol outside invitro after a 24-hour incubation . The reduction increased with the increase incubation period up to 48 hours The highest cholesterol reducing bacteria were Bifidobacterium sp. However the least reduction was caused by Lact. bulgaricus and Strep thermophilus.